Pemanfaatan Panel Surya untuk Usaha Indekos guna Menambah Nilai Ekonomi yang Ramah Lingkungan - Kurniawan, T. Agung; Sundari, Sri; Kuntjoro, Yanif; Dinanti, Prisila; Sianipar, Leo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Energy needs are increasing every year, on the other hand energy stocks from fossil materials will be depleted if they continue to be used, because energy from fossil sources cannot be renewed. Therefore, today we must utilize energy from new renewable energy sources because it can be renewed and environmentally friendly. Solar energy cannot be directly used and must be converted first into electrical energy. To convert in the form of electrical energy the components needed to convert solar energy into electrical energy are called solar cells. With the need for sufficiently large electrical energy, private homes should have switched and must take advantage of the existing potential of solar energy to be converted into electrical energy in meeting the electricity needs needed daily. This research focuses on descriptive research. By using a quantitative descriptive method, it is expected to produce research results that are truly in accordance with field conditions. The results of the calculations that can be concluded are that the investment costs are only around 4.3 years with an average use of panels that can reach a period of 25 years, and the power generated in 1 year is 18,885 kWh. Then the revenue generated from PLTS is IDR 38,525,400. Keywords: Cost, Economy, Energy, Solar Panels.